Assessment of digital terrain model (DTM) generate from UAV aerial image using photogrammetric image processing module / Intan Shahirah Sobri - Sobri, Intan Shahirah (2020)
The Digital Terrain Model (DTM) were presented about bare surface of the earth. It is produce DTM from data Unmanned Aerial Vehicle (UAV). However, the lack of processing will caused error and the result produce erroneous DTM result (Zietara 2017). Therefore, this study to assess the accuracy of the Digital Terrain Model (DTM) on a map generated from UAV Aerial Images in Uitm Arau Perlis. The objective of this study to apply the photogrammetry image processing process in production of Digital Terrain Model (DTM) using UAV Aerial Image and to analyze accuracy of Digital Terrain Model (DTM). These images were processed using Agisoft Photoscan. Eight (8) point were placed as Ground Control Point (GCP) and coordinate measured using static method using Trimble R6 GPS instruments. Besides,30 station of check points were establish at this area through the method GPS RTK net in order to determine accuracy of Ortho photo and DTM. The overall result of DTM are between7m to 40 m. The result for mapping accuracy assessment based on RMSE, which is the error should below than 0.2meter for xy Coordinate and for vertical below than 0.4meter.The final result of this research show that the DTM are processing in 3 different method processing. There are unclassify, random classify and classify. The accuracy of DTM coordinate differential between map and survey check point were analyzed In conclusion, the Digital Terrain Model (DTM) are processing from UAV Aerial Image that can be use for surveyor to analyse the elevation of earth. This is because UAV can generate accurate of DTM.